Examining Unilateral and Bilateral Exercises through the Load-velocity Relationship - Martínez-Rubio, Carlos; Baena-Raya, Andrés; Díez-Fernández, David M.; Rodríguez-Pérez, Manuel Antonio; Pareja-Blanco, Fernando (International Journal of Sports Medicine, 2023)
This study aimed to examine the load-velocity (L-V) relationship in the bench-press (BP) and leg-press (LP) exercises performed unilaterally, and compared this unilateral L-V relationship with the bilateral variants. Nineteen men (age=23.5±2.1 years) completed two incremental tests in BP and LP, performed bilaterally and unilaterally, across two sessions with a 48-hour rest period. We found a close relationship between medium propulsive velocity (MPV) and %1RM in unilateral BP (R2  =0.97, SEE=0.06 m·s-1) and LP (R2=0.96, SEE=0.06 m·s-1). No significant differences were observed between the preferred and non-preferred sides in the L-V relationship for either exercise. Additionally, higher velocities were achieved in unilateral exercises compared to bilateral exercises, particularly with light and moderate loads (30–70%1RM) in BP (p<0.05) and with light loads (30–45%1RM) in LP (p<0.05). Close L-V relationships were observed in unilateral exercises, without differences in the L-V relationships between preferred and non-preferred sides despite the interlimb asymmetries in the absolute strength values. Interestingly, lower velocities were observed at light loads (~30–45% 1RM) for bilateral compared to unilateral exercises, which could be explained by different strength deficits for these exercises.
Keywords: resistance training; muscle strength; movement velocity; strength assessment; asymmetries; bilateral deficit